Care-limiting decisions in acute stroke and association with survival: analyses of UK national quality register data. Issue 3 (April 2016) - Parry-Jones, Adrian R; Paley, Lizz; Bray, Benjamin D; Hoffman, Alex M; James, Martin; Cloud, Geoffrey C; Tyrrell, Pippa J; Rudd, Anthony G; ,
Background: Prognosis after intracerebral hemorrhage (ICH) is poor and care-limiting decisions may worsen outcomes. Aims: To determine whether in current UK stroke practice, key acute care decisions are associated with stroke subtype (ICH/ischemic) and whether these decisions are independently associated with survival. Methods: We extracted data describing all stroke patients included in a UK quality register between 1 April 2013 and 31 March 2014. Key care decisions in our analyses were transfer to higher level care on admission and palliation in the first 72 h. We used multivariable regression models to test for associations between stroke subtype (ICH/ischemic), key care decisions, and survival. Results: A total of 65, 818 patients were included in the final analysis. After ICH ( n  = 7020/65, 818, 10.7%), 10.5% were palliated on the day of admission and 19.3% by 72 h (vs. 0.7% and 3.3% for ischemic stroke). Although a greater proportion were admitted directly to higher level care after ICH (3.7% vs. 1.5% for ischemic stroke), ICH was not independently associated with the decision to admit to higher level care (adjusted odds ratio (OR): 1.12, 95% confidence interval (95%CI): 0.95–1.31, p  = 0.183). However, ICH was strongly associated with the decision to commence palliative care on the day of admission (OR: 7.27, 95%CI: 6.31–8.37, p  < 0.001). Palliative care was independently associated with risk of death by 30 days regardless of stroke subtype. Conclusions: When compared to ischemic stroke, patients with ICH are much more likely to commence palliative care during the first 72 h of their care, independent of level of consciousness, age, and premorbid health.